Enhanced quantum sieving of hydrogen isotopes via molecular rearrangement of the adsorbed phase in chabazite. Issue 41 (28th April 2020) - Radola, Bastien; Bezverkhyy, Igor; Simon, Jean-Marc; Salazar, José Marcos; Macaud, Mathieu; Bellat, Jean-Pierre
Abstract : Adsorption isotherms of H2 and D2 in pure silica chabazite at 47 K show an unexpected step associated with an increase of the D2 /H2 adsorption selectivity due to molecular rearrangement. Abstract : Coadsorption experiments reveal an unexpected increase of the D2 /H2 selectivity with loading in pure silica chabazite at 47 K. This effect is correlated with the appearance of a step in the adsorption isotherms of H2 and D2 . Grand canonical Monte Carlo simulations show that this phenomenon is related to a molecular rearrangement of the adsorbed phase induced by its strong confinement. In the case of a H2 and D2 mixture, this rearrangement favors the adsorption of D2 having a smaller size due to quantum effects.